Genes Associated with the Flax Plant Type (Oil or Fiber) Identified Based on Genome and Transcriptome Sequencing Data - Liubov V. Povkhova; Nataliya V. Melnikova; Tatiana A. Rozhmina; Roman O. Novakovskiy; Elena N. Pushkova; Ekaterina M. Dvorianinova; Alexander A. Zhuchenko; Anastasia M. Kamionskaya; George S. Krasnov; Alexey A. Dmitriev (Plants, 2021)
As a result of the breeding process, there are two main types of flax (Linum usitatissimum L.) plants. Linseed is used for obtaining seeds, while fiber flax is used for fiber production. We aimed to identify the genes associated with the flax plant type, which could be important for the formation of agronomically valuable traits. A search for polymorphisms was performed in genes involved in the biosynthesis of cell wall components, lignans, fatty acids, and ion transport based on genome sequencing data for 191 flax varieties. For 143 of the 424 studied genes (4CL, C3′H, C4H, CAD, CCR, CCoAOMT, COMT, F5H, HCT, PAL, CTL, BGAL, ABC, HMA, DIR, PLR, UGT, TUB, CESA, RGL, FAD, SAD, and ACT families), one or more polymorphisms had a strong correlation with the flax type. Based on the transcriptome sequencing data, we evaluated the expression levels for each flax type-associated gene in a wide range of tissues and suggested genes that are important for the formation of linseed or fiber flax traits. Such genes were probably subjected to the selection press and can determine not only the traits of seeds and stems but also the characteristics of the root system or resistance to stresses at a particular stage of development, which indirectly affects the ability of flax plants to produce seeds or fiber.